2018
DOI: 10.5005/jp-journals-10005-1513
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Deleterious Oral Habits among 3- to 5-yearold Preschool Children in Bhubaneswar, Odisha, India

Abstract: AimOral habits during and beyond preschool age are one of the important etiological factors in developing malocclusion and other ill effects on orofacial structures. The objective of the present study was to know the prevalence of deleterious oral habits among 3- to 5-year-old preschool children in Bhubaneswar, Odisha, India.Materials and methodsThis cross-sectional study was conducted among preschool children, in the age group of 3 to 5 years in the city of Bhubaneswar, Odisha, India. To carry out this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 109 publications
0
14
0
1
Order By: Relevance
“…In this study, all the participants have only one oral habit. In another study, it was found that the majority had only one oral habit present, however 69 (38%) children presented with more than one oral habit (Dutta and Verma, 2018). Lip biting was found to be the most prevalent habit (Murrieta-Pruneda, 2009).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In this study, all the participants have only one oral habit. In another study, it was found that the majority had only one oral habit present, however 69 (38%) children presented with more than one oral habit (Dutta and Verma, 2018). Lip biting was found to be the most prevalent habit (Murrieta-Pruneda, 2009).…”
Section: Resultsmentioning
confidence: 92%
“…Oral Habits are acquired by automatism represented by an altered pattern of muscle contraction with complex characteristics which proceed unconsciously on a regular basis (Dutta and Verma, 2018) Repetitive behaviour of habit is common in the infantile period and most of them are started and stopped spontaneously. The most common and earliest repetitive behaviours seen in the infantile period is digit sucking (Maguire, 2000) Development of these habits are considered to be a part of the normal sequence of maturation process in children however they potentially become a problem / harmful one under the circumstances of mental, physical and socioeconomic stress (Maguire, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parafunctional habits occur due to nonfunctional and unnecessary actions (thumb sucking, lip biting, etc). (Govindaraju, Jeevanandan and E. Subramanian, 2017; Ravikumar, Jeevanandan and Subramanian, 2017)(Christabel and Linda Christabel, 2015)(Packiri, Gurunathan and Selvarasu, 2017) Deleterious oral habits have limited effects on an individual's health, but play a major role in altering the position of the teeth, interferes with the normal growth of jaws and function of the orofacial musculature (Puskaric, Tadic and Djordjevic, 2016;Dutta and Verma, 2018)(Govindaraju, Jeevanandan and E. M. G. Subramanian, 2017b), The factors that determine the effect of oral habits have on the individuals oral health include duration of the habit per day, degree and intensity of the habit (Kamdar and Al-Shahrani, 2015). Oral habits are considered as an abnormal act if it persists after the age of three.…”
Section: Introductionmentioning
confidence: 99%
“…Habits are acquired automatisms,represented by an altered pattern of muscle contraction with complex characteristics, which proceed unconsciously and on a regular basis (Ravikumar, Jeevanandan and Subramanian, 2017). Deleterious oral habits are the common problem of paediatricians which affects the quality of life (Dutta and Verma, 2018). Whereas ,oral habits are repetitive behaviour in the oral cavity that result in the loss of tooth structure and they include digit sucking ,lip sucking, lip biting, nail-biting , bruxism, self-injurious habits, mouth breathing and tongue thrusting (Nowak and Warren, 2000), (Barbosa and Gavião, 2008).…”
Section: Introductionmentioning
confidence: 99%